Impact of exercise changes on body composition during the college years–a five year randomized controlled study - Kemmler, Wolfgang; von Stengel, Simon; Kohl, Matthias; Bauer, Julia (BMC Public Health, 2016)
BACKGROUND: Observational studies have consistently reported severe weight gains during the college years; information about the effect on body composition is scarce, however. Thus, the aim of the study was to determine the effect of exercise changes on body composition during 5 years at university. METHODS: Sixty-one randomly selected male and female dental (DES; 21 ± 3 years., 22 ± 2 kg/m(2)) and 53 sport (physical education) students (SPS; 20 ± 2 years., 22 ± 3 kg/m(2)) were accompanied over their 5-year study program. Body mass and body composition as determined via Dual-Energy x-ray-absorptiometry (DXA) at baseline and follow-up were selected as primary study endpoints. Confounding parameters (i.e., nutritional intake, diseases, medication) that may affect study endpoints were determined every two years. Endpoints were log-transformed to stabilize variance and achieve normal distributed values. Paired t-tests and unpaired Welch-t-tests were used to check intra and inter-group differences. RESULTS: Exercise volume decreased significantly by 33% (p < .001) in the DES and increased significantly (p < .001) in the SPS group. Both cohorts comparably (p = .214) gained body mass (SPS: 1.9%, 95%-CI: 0.3-3.5%, p = .019 vs. DES: 3.4%, 1.4-5.5%, p = .001). However, the increase in the SPS group can be completely attributed to changes in LBM (2.3%, 1.1-3.5%, p < 0.001) with no changes of total fat mass (0.6%, -5.0-6.5%, p = 0.823), while DES gained total FM and LBM in a proportion of 2:1. Corresponding changes were determined for appendicular skeletal muscle mass and abdominal body-fat. Maximum aerobic capacity increased (p = .076) in the SPS (1.6%, -0.2-3.3%) and significantly decreased (p = .004) in the DES (-3.3%, -5.4 to -1.2%). Group differences were significant (p < .001). With respect to nutritional intake or physical activity, no relevant changes or group differences were observed. CONCLUSION: We conclude that the most deleterious effect on fatness and fitness in young college students was the pronounced decreases in exercise volume and particularly exercise intensity. TRIAL REGISTRATION: NCT00521235; "Effect of Different Working Conditions on Risk Factors in Dentists Versus Trainers. A Combined Cross sectional and Longitudinal Trial with Student and Senior Employees."; August 24, 2007.
EVALuna2:33292